Edukasi Interaktif untuk Menumbuhkan Motivasi Belajar Anak Pada Siswa Kelas VI SDN 6 Tanjung Lago - Resa Putri Raflesia; Mutia Mawardah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Learning media is an important part of a learning process, and according to the method, a more creative, interactive, and enjoyable learning strategy is needed. One relevant approach is interactive education, which involves educational games, mini-discussions, simple quizzes, interactive story reading, group games, and creative activities such as drawing or practicing counting through visual media. The methods used are systematically arranged and adapted to the conditions and needs of class students, namely: Observation and Recognition of Student Conditions; Planning Interactive Educational Activities; Implementation of Interactive Educational Activities; Simple Reflection and Evaluation; and Preparation of Activity Reports. The application of interactive education makes the learning atmosphere more lively and less monotonous. Students do not only act as recipients of material, but are directly involved in each activity. This activity not only increases students' awareness of the importance of learning motivation but also creates a more supportive and encouraging classroom atmosphere.